2021
DOI: 10.1038/s41598-021-01224-3
|View full text |Cite
|
Sign up to set email alerts
|

Improved production of the non-native cofactor F420 in Escherichia coli

Abstract: The deazaflavin cofactor F420 is a low-potential, two-electron redox cofactor produced by some Archaea and Eubacteria that is involved in methanogenesis and methanotrophy, antibiotic biosynthesis, and xenobiotic metabolism. However, it is not produced by bacterial strains commonly used for industrial biocatalysis or recombinant protein production, such as Escherichia coli, limiting our ability to exploit it as an enzymatic cofactor and produce it in high yield. Here we have utilized a genome-scale metabolic mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 66 publications
2
12
0
Order By: Relevance
“…Recently, Shah et al showed that the F 420 yield in E. coli can be increased up to 2.33 μmol L –1 by varying carbon sources, which demonstrates the potential for improving non-natural cofactor production by using simple methods. 14 The FOP yield presented here closely resembles the F 420 yield from M. smegmatis , which is 1.43 μmol L –1 . The estimated FOP productivity per unit of time (0.078 μmol L –1 h –1 ), however, is much higher than that of F 420 by M. smegmatis .…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Recently, Shah et al showed that the F 420 yield in E. coli can be increased up to 2.33 μmol L –1 by varying carbon sources, which demonstrates the potential for improving non-natural cofactor production by using simple methods. 14 The FOP yield presented here closely resembles the F 420 yield from M. smegmatis , which is 1.43 μmol L –1 . The estimated FOP productivity per unit of time (0.078 μmol L –1 h –1 ), however, is much higher than that of F 420 by M. smegmatis .…”
Section: Discussionsupporting
confidence: 71%
“…coli can produce the cofactor as well, albeit with lower yields than that produced naturally in M. smegmatis (∼27 nmol L –1 of culture in E. coli, compared to 1.43 μmol L –1 in M. smegmatis ). ,, The heterologous production yield of the cofactor can be improved through optimizing growth conditions as it was demonstrated in a follow-up study …”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Alongside recent work incorporating F420 biosynthesis into common microbial cell factories, such as E. coli, 13,[23][24][25] this work should facilitate the wider adoption of FDORs as biocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Using induced-fit computational docking, plausible Michaelis structures were obtained from which we could rationalize the observed enantioselectivity and propose a mechanism for the reduction of the substrates. Alongside recent work incorporating F 420 biosynthesis into common microbial cell factories, such as E. coli , 13, 2325 this work should facilitate the wider adoption of FDORs as biocatalysts.…”
Section: Introductionmentioning
confidence: 99%